Women's delinquency in work environments in the light of criminological teachings and criminal regulations - Mahmoudi, Nasrin; Shams Natari, Mohammadebrahim; Mirkhalili, Seyed Mahmoud (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The present study was conducted with the aim of explaining the delinquency of women in the workplace in the light of criminology teachings and criminal regulations. Research method: The current research method was library and descriptive-analytical. Findings: Committing crime and wrongdoing is not specific to a certain social stratum or gender. Men or women in different economic and social positions find opportunities for wrongdoing in different ways. Unbalanced increase in population and its unbalanced distribution, economic crises, increase in unemployment, mass migrations, marginalization in big cities, ethnic strife and increase in crime are among the issues that have attracted the attention of many experts on social issues. Conclusion: Women's delinquency is a very complex social phenomenon that is seen in different ways in different social environments. The definition of delinquent and delinquent behavior in any society is determined by the legal laws and social norms of that society. Although in most societies, delinquency is defined as a behavior that can be punished by the law, but the legal concept is not enough to explain it. Women's delinquency, in the sense of a variable number of acts committed against legal provisions, which can have different natures, is a common aspect of all human societies. Regardless of the nature of the dispute, these actions are almost always defined and predicted by law. One of the areas of women's delinquency is the work environment, and due to its consequences, there is a need to take measures to prevent actions that can be prevented from committing crimes in the field of women's employment by taking advantage of situational and social prevention.